THE ROLE AND IMPORTANCE OF COMMUNICATIVE COMPETENCE IN TECHNICAL EDUCATION - Babaeva Gulnozakhon Latibjonovna (Bright Mind Publishing, 2025)
This article analyzes the essence, significance, and effective methods of developing communicative competence among students of technical higher education institutions. It highlights the importance of improving students’ ability to communicate professionally in foreign languages (particularly English), which plays a key role in increasing their competitiveness in the global labor market.
Keywords: Communicative competence, technical education, communication, speech activity, professional English, interactive methods